New record and diet of the endangered Mau Son Spiny Frog (Quasipaa acanthophora Dubois and Ohler, 2009) in Vietnam - Vien Nguyen; Anh Pham; Truong Nguyen; Tung Tran; Thomas Ziegler; Cuong Pham (Biodiversity Data Journal)
The Mau Son Spiny Frog Quasipaa acanthophora was originally described from Mau Son Mountain, Lang Son Province in 2009 and subsequently recorded in Bac Giang and Quang Ninh Provinces of Vietnam. The species was listed as Vulnerable in the IUCN Red List 2017 and as Endangered in the Vietnam Red Data Book 2024. However, knowledge about diet ecology of the species is virtually lacking.Based on recent fieldwork in northern Vietnam, we herein report a new population of Quasipaa acanthophora from Dong Son–Ky Thuong Nature Reserve in Quang Ninh Province. In addition, we provide data on the diet of Q. acanthophora, based on stomach content analyses of 38 individuals (10 males, 17 females, 11 subadults). A total of 27 prey categories containing 446 items were found in the stomachs of Q. acanthophora. The dominant prey items of the species were Blattodea, Coleoptera (Other Coleoptera), Orthoptera (Gryllidae), Decapoda and Hymenoptera (Formicidae). The most important (IRI) groups amongst the prey of Q. acanthophora were Blattidae (32.67%), followed by Gryllidae (9.11%), other Coleoptera (6.57%), Decapoda (5.72%) and Formicidae (5.61%).